Eksplorasi Etnomatematika Rumah Adat Kepulauan Riau Melayu Atap Limas - Veni Siswiandini (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2023)
Education and culture are two things that cannot be separated in everyday life. In learning mathematics to bridge between culture and education, ethno-mathematics is presented. Unknowingly the basic concepts of mathematics and mathematical ideas have been used by the community to carry out various activities. For example measuring activities (length, area, volume, and weight), architecture in buildings (traditional houses), and games. The aim of this research was to examine and analyze the ethnomathematics exploration of the Riau Archipelago Malay Traditional House with Limas Roof so that basic information in the development of ethnomathematics, especially learning in the field of geometry of Malay pyramid roof houses, can be obtained. This type of research is exploratory research using an ethnographic approach. The results obtained from this study are the use of mathematical elements and concepts in the construction of Malay pyramid-roofed houses. Thus, without studying mathematical concepts, the people of the Riau Archipelago have applied mathematical concepts in their daily lives. Thus, it is proven that the activities of the people of the Riau Archipelago have ethnomathematics forms that are owned and developed, namely: 1) design activities for the construction of Malay pyramid-roofed houses; 2) the activity of making motif patterns on the roof carvings of Malay roofs of pyramid roofs; 3) the activity of making patterns on the doors and windows of Malay houses with pyramid roofs; and 4) design activities for making Malay staircases with pyramid roofs.